Crystal structure of Clostridium botulinum neurotoxin protease in a product-bound state: Evidence for noncanonical zinc protease activity - Segelke, Brent (National Academy of Sciences, 2004)
Clostridium botulinum neurotoxins (BoNTs), the most potent toxins known, disrupt neurotransmission through proteolysis of proteins involved in neuroexocytosis. The light chains of BoNTs are unique zinc proteases that have stringent substrate specificity and require exceptionally long substrates. We have determined the crystal structure of the protease domain from BoNT serotype A (BoNT/A). The structure reveals a homodimer in a product-bound state, with loop F242–V257 from each monomer deeply buried in its partner's catalytic site. The loop, which acts as a substrate, is oriented in reverse of the canonical direction for other zinc proteases. The Y249–Y250 peptide bond of the substrate loop is hydrolyzed, leaving the Y249 product carboxylate coordinated to the catalytic zinc. From the crystal structure of the BoNT/A protease, detailed models of noncanonical binding and proteolysis can be derived which we propose are also consistent with BoNT/A binding and proteolysis of natural substrate synaptosome-associated protein of 25 kDa (SNAP-25). The proposed BoNT/A substrate-binding mode and catalytic mechanism are markedly different from those previously proposed for the BoNT serotype B.